Sovereign stress, unconventional monetary policy, and SME access to finance - Annalisa Ferrando; Alexander Popov; Gregory F. Udell (European Central Bank (ECB), 2015)
We investigate the effect of sovereign stress and of unconventional monetary policy on small firms' financing patterns during the euro area debt crisis. We find that after the crisis started, firms in stressed countries were more likely to be credit rationed, both in the quantity and in the price dimension, and to increase their use of debt securities. We also find evidence that the announcement of the ECB's Outright Monetary Transactions Program was followed by an immediate decline in the share of credit rationed firms and of firms discouraged from applying. In addition, firms reduced their use of debt securities, trade credit, and government-subsidized loans. Firms with improved outlook and credit history were particularly likely to benefit from easier credit access.
Keywords: D22; E58; G21; H63; 330; Credit Access; SMEs; sovereign debt; unconventional monetary policy